The X-ray absorption immersion technology for enrichment of diamond ores: Physical foundations and practical implementation - Kuptsov Vladimir (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2025)
The paper presents physical principles of X-ray absorption immersion technology (XRAIT) based on recording X-ray radiation passed through diamond-containing ore, pore spaces between the pieces of which are preliminarily filled with an immersion medium (IM). The energy range of X-ray photons where the diamond is more transparent than the ore components has been determined. Based on the proposed approximation of the mass attenuation coefficients of elements by the sum of two power functions, a justification for a conscious choice of the mass attenuation coefficient of the IM equal to the average value for all ore components was carried out taking into account their weight content. An optimal composition of the IM in the form of a bulk material, namely aluminum-zinc alloy powder, was proposed. Experiments conducted on a developed and manufactured prototype of the separator confirmed the possibility of using the XRAIT with significant advantages over analogues.